The role of purchasing interest: do halal certification and halal awareness determine purchasing decisions? - Purnomo, Irfan Agung; Pratikto, Heri; Suharsono, Naswan (Manajemen dan Bisnis, 2024)
Developing distribution marketing is the biggest challenge for MSME businesses in the Blitar district. Demands policy from the government For all products circulating on the modern market must Already have a halal label in 2024, namely challenge for producers. _ Buying decision be the wrong key For producers measure how much efficient halal certification and halal awareness. The explanatory method with a quantitative approach is this type of research. The population in this study is consumer food light in the district Blitar, for taking samples a purposive random sampling technique, with 2 criteria chosen by the author, found 385 respondents. The path analysis technique is a data analysis technique used in this research. This research result shows that halal certification and awareness have a positive and significant influence on consumers' buying interests, halal certification and buying interests have a positive and significant influence on purchasing decisions, but awareness No there is influence on purchasing decisions. As well as interests buy in a way Partial can mediate between halal certification on purchasing decisions, interests buy capable mediate between halal awareness of purchasing decisions.